Immigration and work - Agius Vallejo, Jody (Research in the sociology of work ;, 2015)
Immigrants and their descendants are growing populations that are rapidly changing the racial/ethnic diversity of the United States and many societies across the globe. People migrate for a multitude of reasons but work - whether in the high-skilled, low-wage, or informal sectors of the economy--or the drive to establish a business, is the primary impetus. The goal of this volume is to bring together new empirical research and theoretical innovations from cutting-edge scholarship concentrating on the intersection of immigration and work. Research in this volume investigates how larger structural inequalities in sending and receiving nations, immigrant entry policies, group characteristics, and micro level processes, such as discrimination and access to ethnic networks, shape labor market outcomes, workplace experiences, and patterns of integration among immigrants and their descendants.